2019
DOI: 10.1152/physrev.00007.2018
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Gating, and Regulation of the CFTR Anion Channel

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR) belongs to the ATP binding cassette (ABC) transporter superfamily but functions as an anion channel crucial for salt and water transport across epithelial cells. CFTR dysfunction, because of mutations, causes cystic fibrosis (CF). The anion-selective pore of the CFTR protein is formed by its two transmembrane domains (TMDs) and regulated by its cytosolic domains: two nucleotide binding domains (NBDs) and a regulatory (R) domain. Channel activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
177
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(188 citation statements)
references
References 283 publications
1
177
0
Order By: Relevance
“…CF is the most common autosomal recessive disorder affecting Caucasians [4], currently affecting >30,000 patients in the US and >70,000 patients worldwide [4,5] with approximately 1000 new cases diagnosed each year [5,6]. The CFTR gene encodes a cAMP-regulated anion channel [7,8] and mutations in the CFTR gene lead to ion imbalance and dysregulation of fluid secretions within a variety of organs including lung, GI and reproductive tracts, pancreas, and skin [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…CF is the most common autosomal recessive disorder affecting Caucasians [4], currently affecting >30,000 patients in the US and >70,000 patients worldwide [4,5] with approximately 1000 new cases diagnosed each year [5,6]. The CFTR gene encodes a cAMP-regulated anion channel [7,8] and mutations in the CFTR gene lead to ion imbalance and dysregulation of fluid secretions within a variety of organs including lung, GI and reproductive tracts, pancreas, and skin [6,9].…”
Section: Introductionmentioning
confidence: 99%
“…CFTR (ABCC7) is the member of the ATP binding cassette (ABC) superfamily. It consists of two transmembrane domains (TMD1 and TMD2), each consisting of 6 TM helices, two nucleotide binding domains (NBD1 and NBD2), and a disordered segment, called regulatory (R) domain [4,5]. The R domain phosphorylation is a prerequisite for channel gating.…”
mentioning
confidence: 99%
“…Hence, our observation that PT disturbs ASL homeostasis might reflect an impact on vectorial ion transport, either activating apical chloride channels or inhibiting ENaC. It has been demonstrated that PT intoxication results in increased intracellular cAMP levels, and CFTR is activated by intracellular cAMP 61 . Yet, future studies, including Ussing chamber measurements, will be required to decipher the impact of PT intoxication on transepithelial ion/water transport in more detail.…”
Section: Discussionmentioning
confidence: 83%